ANALISIS KOMPARATIF PROFITABILITAS AYAM PETELUR KANDANG CLOSE HOUSE DAN OPEN SPACE DI PT. CAHAYA TIGA PUTRI - AL BAASY, MUHAMMAD ARSY; HARYONO, IRANITA; PADAPI, ASTRINI (J-PEN Borneo : Jurnal Ilmu Pertanian, 2024)
This research aims to analyze the comparison of production costs and profitability levels between raising laying hens in Close house  and Open space facilities. The research employed a quantitative descriptive method, conducted from September to November 2023 at PT. Cahaya Tiga Putri, located in Sidenreng Rappang Regency. The analysis included analyzing Return on Assets (ROA), Cost to Revenue Ratio (R/C), Net Profit Margin (NPM), Gross Profit Margin (GPM), and Basic Earning Power (BEP). The research findings indicate that the ROA of Close house  (76,06%) is higher compared to Open space (41,37%). The R/C ratio of Close house  (1,58) is also superior to Open space (1,31). NPM in Close house  (30,08%) exceeds Open space (20,91%), while GPM in Close house  (36,97%) outperforms Open space (25,45%). BEP in Close house  (93,43%) significantly surpasses Open space (50,34%). Thus, this study recommends farmers to switch to Close house  facilities to achieve cost efficiency in production and enhance profitability.